After Cancer Treatment : Heal Faster, Better, Stronger - Silver, J. K. (Julie K.), 1965- (Book collections on Project MUSE., 2006)
Julie Silver draws on her own battle with breast cancer to offer other cancer survivors advice and guidance to help them deal with the physical and emotional effects of the disease and its aftermath.